Emotional dysregulation as trans-nosographic psychopathological dimension in adulthood: A systematic review - Carmassi, Claudia; Conti, Lorenzo; Gravina, Davide; Nardi, Benedetta; Dell'Osso, Liliana (Frontiers in Psychiatry, 2022)
Introduction: Emotional dysregulation (ED) is characterized by inappropriate emotional reactions related to environmental or cognitive stimuli. In most recent years, increasing interest has been devoted to its definition and detection across mental disorders for its detrimental role progressively highlighted in both neurodevelopment and adult psychiatric disorders, with implications on the severity of clinical manifestations. The aim of this systematic review was to evaluate and gather the scientific evidence about ED in adult psychiatric population to elucidate the concept of ED as trans-nosographic entity. Methods: The electronics databases PubMed, Scopus and Web of Science was reviewed to identify studies in accordance with the PRISMA guidelines; at the end of the selection process a total of 29 studies (N= 709; N=658; N=1425) was included. All studies included assessed the presence of ED symptoms, by means of a validate scale in adults (> 18 years of age), in clinically diagnosed patients as well as healthy control participants. Results: Our results suggest ED as a trans-diagnostic factor across multiple mental disorders, such as bipolar disorder, ADHD, ASD, personality disorders; a better definition of this concept could be helpful to interpret and clarify many clinical cases and improve their diagnostic and therapeutic management.